Constructed Islamic Identities in Veiled Woman Represented in Ayat-Ayat Cinta Film (2008) - Sari, Sulhizah Wulan (Fakultas Adab and Humaniora, Universitas Islam Negeri (UIN) Syarif Hidayatullah Jakarta, 2018)
This study discusses the construction of Islamic identities in the figure of veiled woman in Ayat-Ayat Cinta film. The method in this research applies textual analysis method and cultural studies approach in analyzing the film scenes and dialogues based on the theories proposed by Castells on identity formation, Asma Barlas’s feminist hermeneutics of al-Qur’an, gender, and patriarchy. This film shows that Islamic identities as represented by veiled woman is related to the values of man’s power, patriarchal ideology, and social construction. The results of this research proves that the main character as in veiled women is tried side by side with the ideology of patriarchy in struggling for her freedom, justice, and equality with men, so that the veiled woman represents current Islamic values that are harmonious, dynamic, and modern (Pluralist Islam). This study is important to understand variants Islam through Islamic dress, religious practice, and the interpretation of al-Qur’an verse that exist in Indonesia as religious discourse in cultural studies.—Studi ini membahas konstruksi identitas Islam dalam sosok perempuan berjilbab pada film Ayat-Ayat Cinta. Metode dalam penelitian ini menggunakan metode analisis tekstual dan pendekatan kajian budaya dalam menganalisis adegan film dan dialog berdasarkan konsep yang dikemukakan oleh Castells tentang pembentukan identitas, konsep hermeneutik feminis Asma Barlas tentang al-Qur’an, konsep gender, dan patriarki. Dalam film ini menunjukkan bahwa identitas Islam yang diwakili oleh wanita berjilbab terkait dengan nilai-nilai kekuatan laki-laki, ideologi patriarkal, dan konstruksi sosial. Hasil penelitian ini membuktikan bahwa tokoh utama perempuan berjilbab berdampingan dengan ideologi patriarki dalam memperjuangkan kebebasan, keadilan, dan kesetaraannya dengan laki-laki, sehingga perempuan berjilbab mewakili nilai-nilai Islam saat ini, yang harmonis, dinamis, dan modern (Pluralist Islam). Penelitian ini penting untuk memahami variasi Islam melalui busana Islami, praktik keagamaan, dan interpretasi ayat al-Qur’an yang ada di Indonesia sebagai wacana keagamaan dalam kajian budaya.